Formation of Information Consumer Culture in Youth of New Uzbekistan - Xushmatova Gulnoza Norkulovna (International Journal on Integrated Education, 2022)
In this article, the author thinks about what should be done to prevent the fact that today's young people are entering various information streams. Formation of the culture of information consumption is considered the main task.